Brake Current Control System Modeling Using Linear Quadratic Regulator (LQR) and Proportional integral derivative (PID) - Nugraha, Anggara Trisna; Pratiwi, Oktavinna Dwi; As’ad, Reza Fardiyan; Athavale, Vijay Anant (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
In the automotive world, each engine has different characteristics and functions, such as engine power, engine torque, and engine fuel emissions. Therefore, the power meter is used as a tool that can provide information about the engine characteristics. To ensure optimal braking performance of the dynamometer.is use eddy current braking dynamometer. his paper provides a comparative analysis between PID control as a classical control technique and modern control technique in the dynamometer eddy current brakes system. Eddy current brakes is a modern braking system that requires a control system to support the braking performance. PID control is often used to be implemented but, in some conditions, it is less optimal. This paper aims to find out that LQR and PID can support the performance of the Eddy current brakes dynamometer. And also to find out that LQR is better and optimal than PID controller for braking time response on Eddy current brakes dynamometer. Therefore, it is necessary to develop a modern and optimal control, such as a full state feedback Linear Quadratic Regulator (LQR). The expected result of the research is to produce a control design for the Eddy current brakes dynamometer system using the LQR control method. So that it can be used for the development of the automotive world and is beneficial for the survival of the communityThe comparison of the braking time responses were simulated using Matlab/Simulink. The simulation results show that the response of LQR control is better than the PID, with Ts = 2.12 seconds, Tr = 1.18 seconds, and without overshoot. On the other side, PID control, although having Ts = 0.27 seconds and Tr = 0.18 seconds, there is still an overshoot about 0.7%.